Educational Challenges of Autistic Children within Families in Benue State, Nigeria - B. N, Aondoakaa; E. M., Kembe (Journal of Home Economics Research, 2024)
The study investigated educational challenges of autistic children among families in Benue state. The study was guided by three research questions. Survey research design was used. Population was made up of 96 autistic children, 96 parents, and 22 teachers totalling 214 derived from three institutional homes in Benue State. Educational package for autistic children questionnaire (EPACQ) and Autistic Children Engagement Training Programme (ACETP) were used as the instrument for data collection. Data were analysed using means, standard deviation and bar charts. Results show that the training programme used for educational development of autistic children showed a significant relevance to changes in intellectual behaviour. It follows that the educational challenges faced by autistic children and families can be modified through selected educational programmes. Recommendations include, among others, that curriculum developers need to develop standardized learning materials for autistic children.